2014
DOI: 10.1002/ar.22909
|View full text |Cite
|
Sign up to set email alerts
|

Role of Monochromatic Light on Development of Cecal Tonsil in Young Broilers

Abstract: Previously, the different monochromatic lights have been demonstrated to affect splenocyte proliferation and melatonin (MEL) secretion in broilers. The present study was designed to evaluate the effects of different monochromatic lights on the development and immune function of broiler cecal tonsils, and to disclose the mechanisms underlying these phenomena. A total of 185 broilers (P0) including intact, sham-operated, and pinealectomized groups were exposed to blue light (BL), green light (GL), red light (RL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
4
4
0
Order By: Relevance
“…In an earlier study, Xie et al [215] reported that green light and blue light improved gut mucosal immunity in broiler chickens, and they revealed that the population of iIEL and IgA + cells became evident in the group subjected to green light treatment at an early growth stage (7-21 days) and blue light treatment at a later growth stage (49 days) [215] (Figure 3). These results agree with those obtained by Li et al [78], namely that green light had a positive influence on IgA + cell counts at 14 days of age in the cecal tonsil of chickens. However, the growth induced by light treatment disappeared after pinealectomy, a finding that suggests that melatonin secreted by the pineal gland under the influence of green light is essential for the improvement of immune function [78].…”
Section: Immunological Barriersupporting
confidence: 93%
See 2 more Smart Citations
“…In an earlier study, Xie et al [215] reported that green light and blue light improved gut mucosal immunity in broiler chickens, and they revealed that the population of iIEL and IgA + cells became evident in the group subjected to green light treatment at an early growth stage (7-21 days) and blue light treatment at a later growth stage (49 days) [215] (Figure 3). These results agree with those obtained by Li et al [78], namely that green light had a positive influence on IgA + cell counts at 14 days of age in the cecal tonsil of chickens. However, the growth induced by light treatment disappeared after pinealectomy, a finding that suggests that melatonin secreted by the pineal gland under the influence of green light is essential for the improvement of immune function [78].…”
Section: Immunological Barriersupporting
confidence: 93%
“…These results agree with those obtained by Li et al [78], namely that green light had a positive influence on IgA + cell counts at 14 days of age in the cecal tonsil of chickens. However, the growth induced by light treatment disappeared after pinealectomy, a finding that suggests that melatonin secreted by the pineal gland under the influence of green light is essential for the improvement of immune function [78]. These results agree with those obtained by Li et al [78], namely that green light had a positive influence on IgA + cell counts at 14 days of age in the cecal tonsil of chickens.…”
Section: Immunological Barriersupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, replacing white light with blue light have been reported to modify the activities of heat shock biomarkers, and confer higher resistance to heat stress on broilers ( Abdo et al, 2017 ). These beneficial effects might be attributable to the enhanced expression of clock genes in the pineal gland and upregulation of melatonin synthesis induced by green or blue lighting, therefore contributing to improve antioxidant capacity and immune function of broilers ( Ke et al, 2011 ; Li et al, 2014 ; Jiang et al, 2016 ).…”
Section: Effects Of Light Parameters On Health and Growth Of Broilersmentioning
confidence: 99%
“…However, recent studies showed that UV light lowers the H/L ratio in laying hens [135] and broilers [136]. The number of intraepithelial lymphocytes and IgA+ cells in cecal tonsils and in the small intestine were shown to be higher under green and blue light compared to red light [137,138]. Studies investigating the functionality of immune cells emerge with a clearer picture.…”
Section: Light Color/wavelengthmentioning
confidence: 99%